Multilayer blown film
By using metallocene-catalyzed bimodal propylene-1-butene random copolymer as the base layer and a thin sealing layer based on polyethylene, the shortcomings of the existing multi-layer blown film in the sealing performance, optical performance and mechanical properties are solved, and excellent sealing performance and good optical performance are achieved.
Patent Information
- Application Number
- CN202180016373.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-24
- Filing Date
- 2021-03-17
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-03-17
AI Technical Summary
The existing multi-layer blown films have shortcomings in sealing performance, optical performance and stiffness/impact force balance, especially the high sealing starting temperature and it is difficult to achieve excellent mechanical properties and good optical performance at the same time.
A multi-layer blown film consisting of a thin sealing layer based on polyethylene and a base layer based on metallocene catalyzed bimodal propylene-1-butene random copolymer is improved by optimizing the polymer composition and structure.
The excellent sealing performance of multi-layer blown film is achieved, low sealing starting temperature, good optical performance and improved stiffness/impact force balance, improving the overall performance of the film.
Smart Images

Figure BDA0003811346630000061 
Figure BDA0003811346630000161 
Figure BDA0003811346630000162
Abstract
Description
Technical Field
[0001] The present invention relates to a multilayer blown film comprising at least two layers, namely a sealing layer (SL) comprising a metallocene-catalyzed linear low-density polyethylene (mLLDPE) and at least one base layer (BL) or core layer (CL) comprising a metallocene-catalyzed bimodal propylene-1-butene copolymer (mC3C4). Background Art
[0002] Nowadays, the demands on packaging materials are very high. The packaging industry often requires multiple properties that conflict with each other. Often, high stiffness and toughness as well as excellent sealing properties and good optical properties are required at the same time. In order to achieve these different properties, pure components are rarely used, but rather combinations of different polymer components. Those skilled in the art mainly use two different methods: (a) blending two or more polymers to form a multiphase structure, or (b) producing a multilayer structure with different materials that provide different functions. They are both used in industry, the latter being more popular because the choice of materials is more diverse and there is no need to consider the demanding technical issues of complex polymer blends. Using multilayer structures known in the art, multilayer films with good properties for the packaging industry have been obtained. One of the typical examples is a combination of two polyethylene layers, one of which is based on a polyethylene layer with a density of about 0.918 g / cm 3 The combination is based on a sealing layer of linear low-density polyethylene (LLDPE) of 100% and a core layer based on medium-density polyethylene (MDPE) or linear low-density polyethylene (LLDPE) with higher density, which improves the mechanical properties. The disadvantage of this combination is that due to the use of polyethylene with higher density, an acceptable stiffness / toughness balance is achieved at the expense of optical properties.
[0003] Of course, polypropylene, especially polypropylene containing higher α-olefins (such as 1-hexene), can also be used in the film manufacturing of packaging systems. This polypropylene has shown good sealing properties and is therefore often used as a sealing layer in multilayer films. However, the overall performance of this multilayer film, especially in terms of sealing properties, is not as good as that of polyethylene multilayer systems.
[0004] Several multilayer films consisting of a combination of polypropylene (PP) and different types of polyethylene (PE) layers are known for various applications, as outlined for example in the Borealis sales brochure “Polypropylene Blown Film” FF BROCH 121 GB 201008 BB.
[0005] Many patents describing multilayer film structures are also known.
[0006] For example, EP 2540496 discloses a multilayer blown polymer film comprising: (a) a core layer (CL) selected from the group consisting of polyvinyl alcohol, polyacrylate, polyamide, polyethylene terephthalate, polyolefin (PO) and mixtures thereof, and (b) a sealant layer (SL) comprising a propylene copolymer composition (P) comprising:
[0007] (c1) has a comonomer content of 3.0 to 8.0 wt. %, the comonomer being a C5 to C12 α-olefin,
[0008] (c2) comprising a polypropylene (A) and a propylene copolymer (B) in a weight ratio [(A) / (B)] of 20 / 80 to 80 / 20, wherein the polypropylene (A) is a propylene homopolymer (HA) or a propylene copolymer (CA) having a comonomer content of less than 4.0 wt.-%, the comonomer being a C5 to C12 α-olefin, and the propylene copolymer (B) having a comonomer content of 4.0 to 20.0 wt.-%, the comonomer being a C5 to C12 α-olefin, and
[0009] (c3) The ratio MFR A / MFR P ≤ 1.0 is satisfied.
[0010] Thus, EP 2540496 discloses a multilayer film wherein the sealing layer is based on PP and the core layer is a polymer different from the PP of the sealing layer.
[0011] According to an embodiment, these structures have a seal initiation temperature (SIT) of at least 107° C., which is still considered too high for many purposes.
[0012] Another example is EP 2994309, which claims a multilayer polymer film comprising a sealing layer and a base layer, wherein the sealing layer comprises a polypropylene (SL-PP) containing 0.5 to 25 wt% of comonomer units derived from ethylene, and 0.5 to 4.0 mol% of comonomer units derived from at least one C5-12 alpha-olefin, XCS ≥ 20 wt%, and the xylene solubles have an amount of ethylene derived comonomer units of 4 to 50 wt%, meeting the relationship C2 XS×XS / 100 / C2 total ≥ 0.90 and the relationship: C5-12 XS×XS / 100 / C5-12 total ≤ 0.30. Here again, the focus is on a sealing layer based on a specific PP copolymer.
[0013] According to the embodiments, these structures have a sealing initiation temperature (SIT) of at least 88° C. but mainly above 100° C. However, the high content of extractables (XCS) limits the applicability of these structures.
[0014] In WO 2007085283 A1, a three-layer (BAB) blown film is described, with PP homopolymer or PP homo-random polymer as core layer material, and PP random or LLDPE / LDPE blend as skin layer material. The invention aims at higher film stiffness or improved optical properties, such a film is suitable for the manufacture of labels. Sealing and impact properties are not disclosed.
[0015] Although a great deal of development work has been done in the field of multilayer blown films, there is still a need for improved multilayer blown films showing excellent sealing properties, ie low seal initiation temperatures, combined with good optical properties and an improved stiffness / impact balance. Summary of the invention
[0016] It is therefore an object of the present invention to provide a multilayer blown film, in particular an unoriented multilayer blown film, having excellent sealing properties as well as good optical properties and an improved stiffness / impact balance, in particular a high tensile modulus and a high dart impact strength.
[0017] The discovery of the present invention is to provide a multilayer blown film having a thin sealing layer based on polyethylene and a base layer based on a metallocene-catalyzed bimodal propylene-1-butene random copolymer.
[0018] The present invention therefore relates to a multilayer blown film comprising at least two layers, a sealing layer (SL) and a base layer (BL), wherein
[0019] a) The sealing layer (SL) comprises
[0020] (i) at least 90.0 wt.-% up to 100.0 wt.-% of a first polymer composition (PC1), based on the total weight of the sealing layer (SL), the first polymer composition comprising:
[0021] Based on the total weight of the first polymer composition (PC1), at least 70.0 wt% up to 100.0 wt% of a metallocene-catalyzed linear low-density polyethylene (mLLDPE), wherein the density of the metallocene-catalyzed linear low-density polyethylene (mLLDPE) is between 890 and 930 kg / m 3 within the scope of
[0022] 0.0 to a maximum of 30.0 wt. % of other polyethylene polymers of low density polyethylene (LDPE) having a long chain branching (LCB) structure, based on the total weight of the first polymer composition (PC1),
[0023] (ii) and 0.0 to up to 10.0 wt. % of an additive (AD) selected from antioxidants, light stabilizers, acid scavengers, processing aids, antiblocking aids, nucleating agents, slip agents and mixtures thereof, based on the total weight of the sealing layer (SL), and
[0024] b) The base layer (BL) comprises
[0025] (iii) at least 90.0 wt.% up to 100.0 wt.% of a metallocene-catalyzed bimodal propylene-1-butene random copolymer, based on the total weight of the base layer (BL),
[0026] (iv) and 0.0 to up to 10.0 wt. %, based on the total weight of the base layer (BL), of an additive (AD) selected from antioxidants, light stabilizers, acid scavengers, processing aids, antiblocking aids, nucleating agents, slip agents and mixtures thereof.
[0027] In a further embodiment, the multilayer blown film comprises, in addition to the one sealing layer (SL) and the one base layer (BL), at least one further layer, the one further layer being an outer layer (OL), wherein
[0028] c) the outer layer (OL) comprises
[0029] (v) at least 90.0 wt.-% and up to 100.0 wt.-% of a second polymer composition (PC2), based on the total weight of the outer layer (OL), said second polymer composition (PC2) comprising, based on the total weight of the second polymer composition (PC2), at least 90.0 wt.-% and up to 100.0 wt.-% of a polyethylene homopolymer or copolymer,
[0030] (vi) and 0.0 to up to 10 wt. %, based on the total weight of the outer layer (OL), of an additive (AD) selected from antioxidants, light stabilizers, acid scavengers, processing aids, antiblocking aids, nucleating agents, slip agents and mixtures thereof.
[0031] In case the multilayer blown film additionally comprises an outer layer (OL), the stacking order of the at least three layers is (SL) / (BL) / (OL), whereby the base layer (BL) may also be referred to as the core layer (CL).
[0032] Further preferred embodiments are defined in the dependent claims.
[0033] Hereinafter, the present invention will be described in more detail.
[0034] The term "polymer composition (PC)", such as "first polymer composition (PC1)" or "second polymer composition (PC2)", indicates that the composition comprises only polymers, preferably only polyolefins. Thus, the term "polymer composition" excludes, for example, the presence of additives in the composition. However, the polymer composition may of course contain typical impurities, such as catalyst impurities resulting from the polymerization process. Such impurities are considered to be part of the polymer and will not exceed 2.0 wt.-%, based on the total weight of the polymer composition.
[0035] Multilayer film
[0036] The present invention relates to a multilayer blown film comprising at least two layers, namely a sealing layer (SL1) and a base layer (BL).
[0037] Furthermore, the multilayer blown film may comprise at least one further layer, which at least one further layer is an outer layer (OL).
[0038] If such an outer layer (OL) is present, the stacking order of the at least three layers is sealing layer / base layer or core layer / outer layer, (SL) / (BL) / (OL), wherein the base layer (BL) may also be referred to as core layer (CL).
[0039] The multilayer blown film may comprise additional layers, for example between the sealing layer (SL) and the core layer (CL) and / or between the core layer (CL) and the outer layer (OL). Thus, the total number of layers may be up to 9, for example 8, 7, 6, 5 or 4 layers. However, it is preferred that the multilayer film consists of 5 layers, more preferably 2 or 3 layers.
[0040] Thus, in one preferred embodiment, the multilayer blown film consists of a sealing layer (SL) and a base layer (BL), while in another preferred embodiment, the multilayer blown film consists of a sealing layer (SL), a core layer (CL) and an outer layer (OL).
[0041] In the latter case, the sealing layer (SL1) and the outer layer (OL) are the outermost layers, ie the surface layers of the multilayer blown film.
[0042] Preferably, the total thickness of the multilayer blown film is in the range of 20 to 300 μm, more preferably in the range of 25 to 250 μm, still more preferably in the range of 30 to 200 μm, more preferably in the range of 35 to 150 μm, for example in the range of 35 to 100 μm or 40 to 75 μm.
[0043] Preferably, the multilayer blown film is an unstretched film. The term "unstretched" should mean that the multilayer blown film is not dimensionally stretched, as this is the case with biaxially oriented films. Therefore, it is preferred that the multilayer blown film according to the present invention is not biaxially stretched or uniaxially stretched. "Stretching" is a processing step in which the film is stretched more than the normal pull-out effect caused by the film manufacturing. For example, the film in the cast film production line is pulled out and is therefore slightly stretched in the machine direction. A similar effect occurs on the blown film production line where the film bubble of the blown film is pulled out. However, this pull-out effect is not understood as stretching. The stretching is greater than the pull-out that occurs in the cast film production line or the blown film production line. Therefore, the multilayer blown film of the present invention is unstretched. Since the multilayer blown film is produced on the blown film production line, the cooling of the multilayer blown film can be achieved by water cooling or air cooling, the latter being preferred.
[0044] The preparation of multilayer blown films is prior art and is not part of the present invention. For example, multilayer blown films are obtained by a blown film coextrusion process. In a blown film coextrusion process, a melt of polymer material for the base layer (BL) or core layer (CL), for the sealing layer (SL), for the optional outer layer (OL) and optionally for all other layers is extruded through an annular die and blown into a tubular film by forming a film bubble, which collapses between rollers after solidification. Blown coextrusion can preferably be carried out at a temperature in the range of 160 to 240°C and cooled by water or preferably by blowing gas (usually air) at a temperature of 10 to 50°C to provide a frost line height of 0.5 to 8 times the die diameter. The blow ratio should generally be in the range of 1.5 to 4.0, for example 2.0 to 4.0, preferably 2.5 to 3.5.
[0045] Optionally, one or both surfaces of the multilayer blown film can be corona treated or flame treated by one of the known methods. For the corona treatment, the film is passed between two conductor elements used as electrodes, while a high voltage, usually an alternating voltage (about 10,000 V and 10,000 Hz), is applied between the electrodes to enable spraying or corona discharge to occur. Due to the spraying or corona discharge, the air above the film surface is ionized and reacts with the molecules on the film surface, resulting in the formation of polar inclusions in the essentially non-polar polymer matrix. The treatment intensity is within the usual range, preferably 38 to 48 dynes / cm after production.
[0046] The tensile modulus measured at 23° C. on a multilayer blown film having a thickness of 50 μm in the longitudinal and transverse direction according to ISO 527 is preferably in the range of 400 to 1200 MPa, preferably in the range of 500 to 1000 MPa, more preferably in the range of 600 to 800 MPa.
[0047] The multilayer blown film of the present invention has a sealing initiation temperature (SIT) below 100°C, for example below 95°C, more preferably below 90°C (measured on a 50 μm multilayer blown film as described in the experimental part). Although ideally the SIT is as low as possible, a typical lower limit may be 55°C, or 60 or 62°C.
[0048] Preferably, the multilayer blown film thus has a sealing initiation temperature (SIT) in the range of 55 to 100°C, more preferably in the range of 60 to 95°C, even more preferably in the range of 62 to 90°C.
[0049] The multilayer blown film may also have a haze of 10.0% or less, preferably 8.0% or less, more preferably 5.0% or less (measured on a 50 μm multilayer blown film according to ASTM D 1003-00).
[0050] Therefore, the haze of the multilayer blown film is preferably in the range of 0.5% to 10.0% or less, more preferably in the range of 1.0% to 8.0% or less, and even more preferably in the range of 1.5% to 5.0% or less.
[0051] Furthermore, the multilayer blown film may have a transparency of at least 95.0% up to 100.0%, preferably at least 98.0% up to 100.0%, even more preferably at least 99.0% up to 100.0% (measured according to ASTM D 1003-00 on 50 μm multilayer blown film).
[0052] Furthermore, it is preferred that the multilayer blown film has a dart drop impact strength (DDI) measured according to ASTM D1709 method A on a 50 μm multilayer blown film of at least 150 g and up to 550 g, more preferably in the range of 200 to 500 g, still more preferably in the range of 250 to 450 g, for example in the range of 290 to 400 g.
[0053] From another perspective, there is a continuous need to provide films that exhibit improvements in more than just one or two of these mechanical or optical properties. Thus, there is a need to provide products with well-balanced and continuously improving overall properties.
[0054] This improvement in the overall performance of the blown film can be expressed in terms of photomechanical capabilities.
[0055] In view of the present invention, photomechanical ability (OMA) is understood as the ratio of mechanical (especially dart drop impact strength (DDI) and tensile (MD)) behavior to optical performance (i.e. haze), wherein the mechanical performance aims to be as high as possible, while the optical performance in terms of haze is desired to be as low as possible.
[0056] Photomechanical capabilities can be determined by multiplying the tensile modulus (MD) and the dart drop impact strength (DDI; measured according to ASTM D1709 method A on 50 μm multilayer blown films) and comparing this product to the haze measured on 50 μm multilayer blown films.
[0057] Therefore, the photomechanical ability (OMA) can be determined according to the following formula:
[0058]
[0059] Therefore, in another embodiment of the present invention, the photomechanical ability (OMA) of the film measured on a 50 μm multilayer blown film is at least 30,000 [MPa*g / %] up to 90,000 [MPa*g / %], preferably in the range of 40,000 [MPa*g / %] to a maximum of 80,000 [MPa*g / %].
[0060] It will be appreciated that any of the above parameters are measured according to the detailed tests given below. In any parameter where narrower and broader embodiments are disclosed, those embodiments are disclosed in conjunction with the narrower and broader embodiments of the other parameters.
[0061] The layers of the multilayer blown film of the present invention are described in detail below:
[0062] Base layer (BL) or core layer (CL)
[0063] As defined above, the multilayer blown film of the present invention necessarily comprises a base layer (BL) or a core layer (CL), which contributes inter alia to the mechanical and optical properties.
[0064] The term "core layer (CL)" is understood herein as used in the field of packaging technology, ie the term "core layer (CL)" means that this layer forms the middle part of an at least 3-layer blown film.
[0065] The term "base layer" or "core layer (CL)" further indicates that this layer is typically the thickest layer in a multilayer blown film.
[0066] Therefore, it is preferred that the thickness of the base layer (BL) or the core layer (CL) is preferably in the range of 10 to 250 μm, more preferably in the range of 15 to 200 μm, and still more preferably in the range of 20 to 100 μm.
[0067] Furthermore, although the phrase "base layer" or "core layer" is singular, it may refer to one or more layers, for example 2 to 5 layers, i.e. 2, 3, 4 or 5 layers, forming the base layer (BL) or core layer (CL) of the multilayer film. However, each layer that together forms the "base layer" or "core layer" is chemically identical, i.e. produced from the same material. Therefore, for this reason, the base layer (BL) or core layer (CL) is unitary, although in some embodiments, the base layer (BL) or core layer (CL) may include several layers, all of which are made of the same material (i.e. the material defined in more detail below).
[0068] The base layer (BL) or the core layer (CL) comprises, based on the total weight of the base layer (BL) or the core layer (CL), at least 90.0 wt% of a metallocene-catalyzed bimodal propylene-1-butene copolymer (PBC). Preferably, the base layer (BL) or the core layer (CL) comprises a metallocene-catalyzed bimodal propylene-1-butene copolymer (PBC) as the only polymer. Thus, preferably the base layer (BL) or the core layer (CL) comprises, based on the total weight of the base layer (BL) or the core layer (CL), at least 90.0 wt%, more preferably at least 95.0 wt%, still more preferably at least 98.0 wt% of a metallocene-catalyzed bimodal propylene-1-butene copolymer (PBC), and the remainder up to 100 wt%, based on the total weight of the base layer (BL) or the core layer (CL) is additives (AD).
[0069] Typical additives (AD) present in the base layer (BL) or the core layer (CL) are antioxidants, light stabilizers, acid scavengers, processing aids, anti-blocking aids, nucleating agents and slip agents or mixtures thereof. Such additives are known in the art, for example, see "Plastics Additives Handbook" by Hans Zweifel et al., 6th edition, and do not contribute to the present invention.
[0070] Metallocene-catalyzed bimodal propylene-1-butene copolymer (PBC)
[0071] As used herein, the term "propylene-1-butene copolymer" includes polymers polymerized from propylene and 1-butene monomer units. Thus, the propylene-1-butene copolymer consists of propylene and 1-butene monomer units. The propylene-1-butene copolymer is understood to be substantially free of ethylene-derived monomer units, e.g., containing less than 0.1 wt% ethylene, preferably less than 0.01 wt% ethylene, and more preferably less than 0.001 wt% ethylene comonomer.
[0072] The propylene-1-butene copolymer of the present invention contains 85.0 to 98.0 wt% of propylene and 2.0 to 15.0 wt% of 1-butene, based on the total weight of the propylene-1-butene copolymer.
[0073] Preferably, the amount of 1-butene is in the range of 3.0 to 13.0 wt%, more preferably in the range of 3.5 to 11.5 wt%, for example in the range of 4.0 to 11.0 wt%.
[0074] The MFR2 (230° C. / 2.16 kg, ISO 1133) of the propylene-1-butene copolymer is in the range of 0.5 g / 10 min to less than 4.0 g / 10 min.
[0075] The MFR2 of the propylene-1-butene copolymer is preferably in the range of 0.7 to 3.8 g / 10 min, more preferably in the range of 0.8 to 3.5 g / 10 min, further preferably in the range of 0.9 to 3.0 g / 10 min.
[0076] Furthermore, the soluble content of the propylene-1-butene copolymer should be rather low. Thus, the copolymer should have an amount of the xylene cold soluble fraction measured at 25°C according to ISO 16152; 2005 in the range of 0.10 to 2.80 wt.-%, preferably 0.20 to 2.50 wt.-%, more preferably 0.30 to 2.20 wt.-%, even more preferably 0.40 to 2.00 wt.-%, most preferably 0.50 to 1.90 wt.-%.
[0077] Xylene cold solubles are the portion of the polymer that is soluble in cold xylene, determined by dissolving in boiling xylene and allowing the insoluble portion to crystallize from the cooled solution. The xylene soluble fraction contains polymer chains of low stereoregularity and is an indicator of the amount of non-crystalline areas.
[0078] The molecular weight distribution Mw / Mn of the propylene-1-butene copolymer, ie the ratio of the weight average molecular weight Mw to the number average molecular weight Mn, is 2.0 to less than 4.5, preferably in the range of 2.0 to 4.2, such as in the range of 2.5 to 4.0.
[0079] According to one embodiment of the present invention, the propylene-1-butene copolymer has an amount of hexane hot solubles (C6FDA) measured on a 100 μm thick blown film according to FDA 177.1520 in the range of 0.1 to less than 2.0 wt.-%, preferably in the range of 0.2 to 1.7 wt.-%, more preferably in the range of 0.3 to 1.5 wt.-%, even more preferably in the range of 0.4 to 1.4 wt.-%.
[0080] According to another embodiment of the present invention, the propylene-1-butene copolymer preferably has a flexural modulus determined according to ISO 178 in the range of 700 to 1800 MPa, more preferably in the range of 750 to 1600 MPa, even more preferably in the range of 800 to 1400 MPa.
[0081] Alternatively or in addition, the propylene-1-butene copolymer preferably has a 2.0 kJ / m 2 Up to 10.0 kJ / m 2 , preferably 2.5 to 9.0 kJ / m 2 , more preferably 3.0 to 7.0 kJ / m 2 The Charpy notched impact strength at 23° C. determined according to ISO 179 1eA is within a range of 5.0% to 70.0%, preferably 7.5 to 60.0%, more preferably 10.0 to 55.0%, measured on a 1.0 mm thick plate according to ASTM D1033.
[0082] With regard to the comonomer content and / or MFR2 the propylene-1-butene copolymer is preferably bimodal and consists of polymer fractions (A) and (B).
[0083] Thus, the propylene-1-butene copolymer comprises:
[0084] 30.0 to 70.0 wt% of a propylene-1-butene copolymer (A) having an MFR2 of 0.5 to 20.0 g / 10 min and a 1-butene content of 2.0 to 10.0 wt%; and
[0085] 70.0 to 30.0 wt% of a propylene-1-butene copolymer (B) having an MFR2 of 0.5 to 20.0 g / 10 min and a 1-butene content of 3.5 to 20.0 wt%;
[0086] The copolymers (A) and (B) are different and the amounts of (A) and (B) add up to 100.0% by weight.
[0087] (i) Propylene-1-butene copolymer (A)
[0088] The fraction (A) is a propylene-1-butene copolymer component. Usually, the fraction (A) consists of a single propylene-1-butene copolymer.
[0089] The 1-butene content in the copolymer (A) is 2.0 to 10.0% by weight, preferably 3.0 to 9.0% by weight, more preferably 4.0 to 8.0% by weight, based on the total weight of the copolymer (A).
[0090] The melt flow rate (MFR2) of the propylene-1-butene copolymer (A) of the present invention is 0.5 to 20.0 g / 10 min. Typically, the MFR2 of the propylene-1-butene copolymer (A) is 15.0 g / 10 min or less, preferably 12.0 g / 10 min or less, preferably 10.0 g / 10 min or less. The polymer preferably has a minimum MFR2 of 1.0 g / 10 min, for example greater than 1.5 g / 10 min. Therefore, a particularly suitable value for MFR2 is 1.0 to 15.0 g / 10 min, for example 2.0 to 10.0 g / 10 min.
[0091] The propylene-1-butene copolymer fraction (A) is present in an amount of 30.0 to 70.0 wt%, preferably 35.0 to 65.0 wt%, more preferably 37.0 to 60.0 wt%.
[0092] (ii) Propylene-1-butene copolymer (B)
[0093] Fraction (B) is also a propylene-1-butene copolymer component. The 1-butene content in copolymer (B) is 3.5 to 20.0 wt%, preferably 3.7 to 18.0 wt%, more preferably 3.8 to 16.0 wt%, relative to the total weight of copolymer (A).
[0094] The melt flow rate (MFR2) of the propylene-1-butene copolymer (B) of the present invention is 0.5 to 20.0 g / 10 min. Typically, the MFR2 of the propylene-1-butene copolymer (B) is 15.0 g / 10 min or less, preferably 12.0 g / 10 min or less, more preferably 10.0 g / 10 min or less, for example 8.0 g / 10 min or less. Therefore, a particularly suitable value of MFR2 is 0.5 to 10.0 g / 10 min, for example 0.5 to 8.0 g / 10 min.
[0095] The propylene-1-butene copolymer fraction (B) is present in an amount of 70.0 to 30.0 wt%, preferably 65.0 to 35.0 wt%, more preferably 63.0 to 40.0 wt%.
[0096] As described above, the propylene-1-butene copolymer is a bimodal copolymer comprising fractions (A) and (B), and shows double melting peaks (Tm1 and Tm2) in differential scanning calorimetry.
[0097] The Tm1 of the propylene-1-butene copolymer is preferably in the range of 125 to 155°C, more preferably in the range of 130 to 150°C, further preferably in the range of 135 to 145°C, while the Tm2 of the propylene-1-butene copolymer is preferably in the range of 100 to 140°C, more preferably in the range of 105 to 138°C, even more preferably in the range of 107 to 135°C.
[0098] In order to facilitate processing, especially film processing, the propylene-1-butene random copolymer needs to have a suitable crystallization temperature even in the absence of any nucleating agent. Preferably, the propylene-1-butene random copolymer has a crystallization temperature Tc determined by DSC (differential scanning calorimetry) according to ISO 11357 in the range of 85°C to 115°C, more preferably in the range of 90°C to 112°C, for example in the range of 95°C to 111°C.
[0099] It is also preferred that the difference (Tm1-Tc) between the melting temperature Tm1 and the crystallization temperature Tc is quite low. The difference (Tm1-Tc) should preferably be less than 45°C, more preferably in the range of 25°C to 42°C, such as in the range of 28°C to 40°C.
[0100] Furthermore, it is preferred that the propylene-1-butene copolymer as defined above is prepared in the presence of a metallocene catalyst as described in detail in PCT / EP2019 / 081330 or PCT / EP2019 / 081323.
[0101] The propylene-1-butene random copolymer as described above may be prepared by any method known in the art.
[0102] The propylene-1-butene copolymer is preferably prepared by polymerizing propylene and butene in the presence of a metallocene catalyst by a sequential polymerization process comprising at least two reactors connected in series.
[0103] In case the propylene-1-butene copolymer is a bimodal copolymer comprising fractions (A) and (B) as described above, the propylene butene copolymer is preferably produced in a multistage process wherein fractions (A) and (B) are produced in consecutive stages.
[0104] The preparation of multimodal, preferably bimodal, propylene-1-butene copolymers is described in detail in PCT / EP2019 / 081330 or PCT / EP2019 / 081323.
[0105] Multimodal propylene-1-butene copolymers produced in a multistage process are also referred to as "in situ" blends. The resulting final product consists of an intimate mixture of polymers from two or more reactors. The two polymers may have different molecular weight distribution curves, and / or they may differ in comonomer content or type. The final product therefore comprises a mixture of two or more polymers with different properties, i.e. it is a multimodal polymer mixture.
[0106] Sealing layer (SL)
[0107] As mentioned above, the multi-layer film of the present invention necessarily includes a sealing layer (SL).
[0108] The term "sealing layer" is understood herein as used in the field of packaging technology, ie the term "sealing layer" means that the layer can be used for sealing purposes, ie sealing can take place on the surface of the layer or a part of the layer.
[0109] Thus, preferably the sealing layer (SL) forms the outermost layer of the multilayer blown film, thereby forming one of the two surfaces of the multilayer blown film. Still more preferably, the sealing layer (SL) is attached, i.e. joined, to the base layer (BL) or the core layer (CL) of the multilayer blown film. Still more preferably, the sealing layer (SL) forms one of the outermost layers of a three-layer blown film and is attached to the core layer (CL) of the three-layer blown film.
[0110] Preferably, the thickness of the sealing layer (SL) is substantially smaller than the thickness of the base layer (BL) or the core layer (CL) and substantially smaller than the thickness of the entire multilayer blown film. Therefore, it is understood that the thickness of the sealing layer (SL) is in the range of 0.5 to 50 μm, more preferably in the range of 1.0 to 30 μm, and further preferably in the range of 5 to 20 μm.
[0111] The sealing layer (SL) comprises, based on the total weight of the sealing layer (SL), at least 90.0 wt.-% of the first polymer composition (PC1). Preferably, the sealing layer (SL1) comprises the first polymer composition (PC1) as the only polymer component. Therefore, preferably the sealing layer (SL) comprises, based on the total weight of the sealing layer (SL), at least 90.0 wt.-%, more preferably at least 95.0 wt.-%, even more preferably at least 98.0 wt.-% of the first polymer composition (PC1), and the remainder up to 100 wt.-%, based on the total weight of the sealing layer (SL) are additives (AD). Typical additives (AD) present in the sealing layer (SL) are antioxidants, light stabilizers, acid scavengers, processing aids, anti-blocking aids, nucleating agents and slip agents or mixtures thereof. Such additives are known in the art, see for example "Plastics Additives Handbook" by Hans Zweifel et al., 6th edition, and do not contribute to the present invention.
[0112] For the definition of the first polymer composition (PC1), see the information below.
[0113] First polymer composition (PC1)
[0114] As mentioned above, the term "first polymer composition (PC1)" means that the composition comprises only polyethylene. One of the polymers must be a metallocene-catalyzed linear low-density polyethylene (mLLDPE), as defined in more detail below. Therefore, it is preferred that the first polymer composition (PC1) comprises, based on the total weight of the first polymer composition (PC1), at least 70.0% by weight to a maximum of 100.0% by weight, more preferably at least 75.0% by weight to a maximum of 100.0% by weight, still more preferably at least 80.0% by weight to a maximum of 100.0% by weight, even more preferably at least 85.0% by weight to a maximum of 100.0% by weight of a metallocene-catalyzed linear low-density polyethylene (mLLDPE), and based on the total weight of the first polymer composition (PC1), the remainder up to 100.0% by weight is another polyethylene, such as a low-density polyethylene (LDPE) with a long-chain branched (LCB) structure as defined in detail below.
[0115] Therefore, in a preferred embodiment, the first polymer composition (PC1) consists of a metallocene-catalyzed linear low density polyethylene (mLLDPE).
[0116] In another specific preferred embodiment, the first polymer composition (PC1) consists of metallocene-catalyzed linear low density polyethylene (mLLDPE) and low density polyethylene (LDPE).
[0117] In this case, preferably the first polymer composition (PC1) consists of:
[0118] (a) 70.0 to 98.0 wt. %, preferably 75.0 to 95.0 wt. %, still more preferably 80.0 to 92.0 wt. % of a metallocene-catalyzed linear low density polyethylene (mLLDPE), based on the total weight of the first polymer composition (PC1),
[0119] and
[0120] (b) 2.0 to 30.0 wt%, preferably 5.0 to 25.0 wt%, still more preferably 8.0 to 20.0 wt% of low density polyethylene (LDPE), based on the total weight of the first polymer composition (PC1).
[0121] The density of metallocene-catalyzed linear low-density polyethylene (mLLDPE) is between 890 and 930 kg / cm 3 In the range of 900 to 925 kg / m 3 In the range of 910 to 923 kg / m 3 In the range of 912 to 920 kg / m 3 within the range.
[0122] The metallocene-catalyzed linear low-density polyethylene (mLLDPE) comprises at least one comonomer, preferably only one or two comonomers, the latter being particularly preferred. The comonomer is preferably C3 to C 10 α-olefin comonomers. Therefore, it is particularly preferred to use copolymers or terpolymers having only one comonomer, i.e. copolymers of ethylene with two other comonomers. The terpolymer is a particularly preferred linear low-density polyethylene (mLLDPE). Therefore, the metallocene-catalyzed linear low-density polyethylene (mLLDPE) preferably contains only one or two types of C3 to C 10 α-olefin comonomer. Still more preferably, the comonomer is selected from 1-butene, 1-hexene, 1-octene and mixtures thereof. In a preferred embodiment, the comonomer used is 1-octene. In another preferred embodiment, the metallocene-catalyzed linear low density polyethylene (mLLDPE) is a terpolymer consisting of ethylene, 1-butene and 1-hexene.
[0123] The total amount of α-olefin comonomers present in the metallocene-catalyzed linear low density polyethylene (mLLDPE) may range from 1.0 to 10.0 mol%, preferably from 1.5 to 5.0 mol%, even more preferably from 2.0 to 4.5 mol%.
[0124] In the case where the metallocene-catalyzed linear low density polyethylene (mLLDPE) is a terpolymer consisting of ethylene, 1-butene and 1-hexene, it is preferred that the 1-butene content is in the range of 0.05 to 1.0 mol %, more preferably in the range of 0.10 to 0.6 mol %, even more preferably in the range of 0.15 to 0.5 mol %, and the 1-hexene content is in the range of 2.0 to 5.0 mol %, more preferably in the range of 2.4 to 4.5 mol %, even more preferably in the range of 2.6 to 4.0 mol %.
[0125] Furthermore, it is preferred that the melt flow rate MFR2 (190°C, 2.16 kg) of the metallocene-catalyzed linear low density polyethylene (mLLDPE) is in the range of 0.5 to 8.0 g / 10 min, more preferably in the range of 0.8 to 4.0 g / 10 min, even more preferably in the range of 1.0 to 3.5 g / 10 min.
[0126] The metallocene-catalyzed linear low density polyethylene (mLLDPE) may preferably be multimodal, such as bimodal or trimodal, i.e. its molecular weight distribution does not comprise a single peak, but rather, due to the polymer comprising two separately produced components, comprises a combination of two or three peaks (which may or may not be distinguishable) centered around different average molecular weights.
[0127] Multimodal polyethylene is usually made in more than one reactor, each with different conditions. The components are usually so different that they show more than one peak or shoulder in a graph usually given as a result of a GPC (gel permeation chromatography) curve, where d(log(MW)) is plotted as the ordinate against log(MW), where MW is the molecular weight.
[0128] The Mw / Mn of the bimodal or trimodal mLLDPE may be in the range of 2.0 to 7.0, preferably in the range of 2.5 to 6.5, more preferably in the range of 3.0 to 6.0.
[0129] Bimodal metallocene-catalyzed linear low-density polyethylene (mLLDPE) is known in the art and is not the subject of the present invention. In this regard, reference is made to, for example, EP 3 257 895 A1, Example IE1 of EP 3 257 895 A1 or PCT / EP2019 / 086918, for example, a second bimodal terpolymer, or WO 2019 / 081611, Example 3.
[0130] They can be produced in a 2-stage or 3-stage process, preferably comprising at least one slurry reactor (loop reactor), wherein the slurry loop reactor is connected in series with a gas phase reactor (GPR), such that the ethylene polymer leaving the slurry reactor is fed to the GPR to produce bimodal mLLDPE. Alternatively, the process comprises 2 slurry reactors (loop reactors) and one gas phase reactor connected in series, wherein for the 2 slurry reactors the reaction conditions are selected in such a way that the same product (same MFR and density) is produced in both slurry reactors.
[0131] One suitable process is the Borstar PE process.
[0132] The bimodal polyethylene terpolymer preferably comprises at least
[0133] (i) an ethylene polymer component (A) as a lower molecular weight (LMW) component having an MFR2 (according to ISO 1133 at 190°C and 2.16 kg load) of 1.0 to 10.0 g / 10 min and
[0134] (ii) an ethylene polymer component (B) as the higher molecular weight (HMW) component having an MFR2 (according to ISO 1133 at 190°C and 2.16 kg load) of 0.2 to 2.5 g / 10 min, and
[0135] The density of the ethylene polymer component (A) is higher than that of the ethylene polymer component (B); the density of the ethylene polymer component (A) is between 930 and 950 kg / m 3within the range.
[0136] In a preferred embodiment of such terpolymers, the LMW component may be an ethylene homopolymer and the HMW is a terpolymer, especially an ethylene, 1-butene, 1-hexene terpolymer.
[0137] In another preferred embodiment, the LMW component as well as the HMW component may be ethylene copolymers, wherein in the case of a terpolymer it is particularly preferred that the LMW component is an ethylene 1-butene copolymer and the HMW component is an ethylene 1-hexene copolymer.
[0138] An example of such a metallocene-catalyzed linear low-density polyethylene (mLLDPE) is Anteo TM FK1820, a commercially available bimodal ethylene / 1-butene / 1-hexene terpolymer from Borouge, with a density of 918 kg / m 3 , MFR2 is 1.5g / 10min.
[0139] The trimodal metallocene-catalyzed linear low density polyethylene (mLLDPE) can be produced with a 3-stage process, preferably comprising a first slurry reactor (loop reactor 1), wherein the first slurry loop reactor is connected in series with another slurry reactor (loop reactor 2), such that the first ethylene polymer component produced in loop reactor 1 is fed to loop reactor 2. Loop reactor 2 is thereby connected in series to a gas phase reactor (GPR), such that the ethylene polymer leaving the second slurry reactor is fed to the GPR to produce the trimodal mLLDPE. In this case, the reaction conditions in the two slurry reactors are selected such that different products with respect to MFR and density are produced in the two slurry reactors.
[0140] One suitable process is the Borstar PE 3G process.
[0141] The trimodal polyethylene terpolymer preferably comprises at least
[0142] (i) between 10 and <25 wt% of an ethylene polymer component (A) having an MFR2 of 0.1 to 10.0 g / 10 min (according to ISO 1133 at 190°C and 2.16 kg load) and
[0143] (ii) between 10 and <25 wt% of an ethylene polymer component (B) having an MFR2 of 2.0 to 150.0 g / 10 min (according to ISO 1133 at 190°C and 2.16 kg load) and
[0144] (iii) between >50 and 80 wt% of an ethylene polymer component (C) having an MFR2 of 0.1 to 5.0 g / 10 min (according to ISO 1133 at 190°C and 2.16 kg load) and
[0145] The density of the ethylene polymer components (A) and (B) is 925 and 970 kg / m 3 and the density of the ethylene polymer component (C) is between 880 and 920 kg / m 3 between.
[0146] Preferably, the ethylene polymer components (A) and (B) are ethylene 1-butene copolymers, and the ethylene polymer component (C) is an ethylene 1-hexene copolymer or an ethylene, 1-butene, 1-hexene terpolymer.
[0147] In case the first polymer composition (PC1) consists of metallocene-catalyzed linear low density polyethylene (mLLDPE) and low density polyethylene (LDPE) having a long chain branching (LCB) structure, it is preferred that the low density polyethylene (LDPE) comes from a high pressure polymerization process.
[0148] The density of low-density polyethylene (LDPE) is preferably between 910 and 940 kg / m 3 In the range of 915 to 935 kg / m 3 In the range of 918 to 930 kg / m 3 within the range.
[0149] Furthermore, it is preferred that the melt flow rate MFR2 (190° C., 2.16 kg) of the low density polyethylene (LDPE) is in the range of 0.05 to 2.0 g / 10 min, more preferably in the range of 0.10 to 1.8 g / 10 min, even more preferably in the range of 0.15 to 1.5 g / 10 min. Low density polyethylene (LDPE) is known in the art and is not the subject of the present invention. Thus, an example of such a low density polyethylene (LDPE) is the commercial product FT5230 (MFR2: 0.75 g / 10 min; density: 923 kg / m 3 .
[0150] If the first polymer composition (PC1 ) comprises besides the metallocene-catalyzed linear low density polyethylene (mLLDPE) further polymers, like low density polyethylene (LDPE), the first polymer composition (PC1 ) is obtained by typical (melt) blending as known in the art.
[0151] Outer layer (OL)
[0152] As mentioned above, in one embodiment of the present invention, the multilayer blown film comprises at least one additional layer, which is an outer layer (OL). The outer layer (OL) can have any function in the multilayer film according to the present invention. However, it is preferred that the outer layer is a heat insulation layer (HSL) or a second sealing layer (SL2), the latter being particularly preferred.
[0153] Preferably, the outer layer (OL) is the outermost layer.
[0154] In case the multilayer blown film comprises such an outer layer (OL), the stacking sequence of the at least three layers is (SL) / (BL) / (OL), wherein the base layer (BL) may also be referred to as core layer (CL).
[0155] Preferably, the thickness of the outer layer (OL) is substantially smaller than the thickness of the core layer (CL) and substantially smaller than the thickness of the entire multilayer film. Therefore, it is understood that the thickness of the outer layer (OL) is in the range of 0.5 to 50 μm, more preferably in the range of 1.0 to 30 μm, and further preferably in the range of 5 to 20 μm.
[0156] In one embodiment, the sealing layer (SL) and the outer layer (OL) have the same thickness, and in another embodiment, the total thickness of the sealing layer (SL) and the outer layer (OL) is the same as the thickness of the core layer (CL).
[0157] The outer layer (OL) comprises, based on the gross weight of the outer layer (OL), at least 90.0 wt % of the second polymer composition (PC2). Preferably, the outer layer (OL) comprises the second polymer composition (PC2) as the only polymer component. Therefore, preferably the outer layer (OL) comprises, based on the gross weight of the outer layer (OL), at least 90.0 wt %, more preferably at least 95.0 wt %, still more preferably at least 98.0 wt % of the second polymer composition (PC2), and based on the gross weight of the outer layer (OL), the remainder until 100.0 wt % is additives (AD). Typical additives (AD) present in the outer layer (OL) are antioxidants, light stabilizers, acid scavengers, processing aids, anti-blocking aids, nucleating agents and slip agents. Such additives are known in the art, for example, see "Plastics Additives Handbook" by Hans Zweifel et al., 6th edition, and do not contribute to the present invention.
[0158] For the definition of the second polymer composition (PC2), see the information below.
[0159] Second polymer composition (PC2)
[0160] As stated above, the term "second polymer composition (PC2)" means that the composition comprises only polyolefins, such as polyethylene or polypropylene.
[0161] In the case where the outer layer (OL) is a heat insulating layer (HSL), the second polymer composition (PC2) is preferably a second polymer composition (PC2B), and in the case where the outer layer (OL) is a second sealing layer (SL2), the second polymer composition (PC2) is preferably a second polymer composition (PC2A), as defined in detail below.
[0162] In case the outer layer (OL) is a thermal insulation layer (HSL), the thermal insulation layer (HSL) is based on a second polymer composition (PC2B). Preferably, the second polymer composition (PC2B) comprises at least 90.0 wt.-%, more preferably at least 95.0 wt.-%, still more preferably at least 98.0 wt.-% of a polypropylene, based on the total weight of the second polymer composition (PC2B), the polypropylene being:
[0163] (a) a propylene homopolymer (H-PP) having a melting point of at least 158°C;
[0164] or
[0165] (b) a propylene copolymer (R-PP) having
[0166] (i) a melting temperature of at least 150°C, and
[0167] (ii) a comonomer content of not more than 3.5 wt.%, preferably an ethylene content.
[0168] Preferably, the polypropylene is a propylene homopolymer (H-PP).
[0169] Furthermore it is preferred that the propylene homopolymer (H-PP) or the propylene copolymer (R-PP) has a melt flow rate MFR2 (230°C, 2.16 kg) in the range of 0.5 to 20.0 g / 10 min, more preferably in the range of 0.5 to 10.0 g / 10 min.
[0170] In case the outer layer (OL) is a second sealing layer (SL2), said second sealing layer (SL2) is based on a second polymer composition (PC2A).
[0171] The term "second polymer composition (PC2A)" means that the composition comprises only polymers, preferably only polyolefins, and more preferably only polyethylenes. Thus, preferably the second polymer composition (PC2A) comprises at least 70.0 wt.%, more preferably at least 75.0 wt.%, and more preferably at least 80.0 wt.%, of a second linear low density polyethylene (LLDPE2), based on the total weight of the second polymer composition (PC2A), and the remainder up to 100.0 wt.%, based on the total weight of the second polymer composition (PC2A) is a polymer, preferably a polyolefin, more preferably a polyethylene, such as a second low density polyethylene having a long chain branching (LCB) structure.
[0172] In a preferred embodiment the polyethylene (LLDPE2) is a metallocene-catalyzed linear low density polyethylene (mLLDPE) as defined in more detail above for the sealing layer (SL).
[0173] Thus, it is preferred that the second polymer composition (PC2) comprises, based on the total weight of the second polymer composition (PC2), at least 70.0 wt.-% up to 100.0 wt.-%, more preferably at least 75.0 wt.-% up to 100.0 wt.-%, still more preferably at least 80.0 wt.-% up to 100.0 wt.-%, even more preferably at least 85.0 wt.-% up to 100.0 wt.-%, of a metallocene-catalyzed linear low density polyethylene (mLLDPE), and the remainder up to 100.0 wt.-%, based on the total weight of the second polymer composition (PC2) is another polyethylene, such as the low density polyethylene (LDPE) as defined in detail above for the sealing layer (SL).
[0174] Thus, in a preferred embodiment, the second polymer composition (PC2) consists of the metallocene-catalyzed linear low density polyethylene (mLLDPE) as described above for the sealing layer (SL).
[0175] In another specific preferred embodiment, the second polymer composition (PC2) consists of a metallocene-catalyzed linear low density polyethylene (mLLDPE) and a low density polyethylene (LDPE) as described above for the sealing layer (SL).
[0176] The first and second polymer compositions (PC1 and PC2) may be different from each other, or the second polymer composition (PC2) may be the same as the first polymer composition (PC1).
[0177] The metallocene-catalyzed linear low density polyethylene (mLLDPE) in the outer layer (OL) may be different from the metallocene-catalyzed linear low density polyethylene (mLLDPE) in the sealing layer (SL), for example in terms of comonomer content, MFR2, etc., or may be the same in the outer layer (OL) and the sealing layer (SL).
[0178] If the low density polyethylene (LDPE) is part of the second polymer composition (PC2), the low density polyethylene (LDPE) in the outer layer (OL) may be different from the low density polyethylene (LDPE) in the sealing layer (SL), for example in terms of density, MFR2, etc., or may be the same in the outer layer (OL) and the sealing layer (SL).
[0179] Preferably, the second polymer composition (PC2) is identical to the first polymer composition (PC1 ) as defined above.
[0180] Furthermore, the present invention relates to the use of the multilayer blown film according to the invention as packaging material, in particular as packaging material for foods and / or medical products.
[0181] Furthermore, the present invention relates to an article comprising the blown film as defined herein.
[0182] The present invention is further illustrated by the following examples. DETAILED DESCRIPTION
[0183] Example
[0184] 1. Definition / Measurement Method
[0185] Unless otherwise defined, the following definitions of terms and determination methods apply to the above general description of the invention as well as to the following examples.
[0186] Melt flow rate
[0187] The melt flow rate (MFR) is determined according to ISO 1133 and is expressed in g / 10 min. The MFR is an indicator of the fluidity of the polymer and therefore of the processability. The higher the melt flow rate, the lower the viscosity of the polymer. The MFR2 of polypropylene is determined at a temperature of 230°C and a load of 2.16 kg. The MFR2 of polyethylene is determined at a temperature of 190°C and a load of 2.16 kg.
[0188] Calculation of the comonomer content of the second polymer fraction (B) of the propylene-1-butene copolymer:
[0189]
[0190] in
[0191] w(A) is the weight fraction [in wt %] of the first polymer fraction (A),
[0192] w(B) is the weight fraction [in wt %] of the second polymer fraction (B),
[0193] C(A) is the comonomer content [in % by weight] of the first polymer fraction (A),
[0194] C(CP) is the comonomer content of the C3C4 random copolymer [in wt %],
[0195] C(B) is the calculated comonomer content [in wt. %] of the second polymer fraction (B).
[0196] Calculation of the melt flow rate MFR2 (230° C.) of the polymer fraction (B) of the propylene-1-butene copolymer:
[0197]
[0198] in
[0199] w(A) is the weight fraction of polymer fraction A [in wt %]
[0200] w(B) is the weight fraction of polymer fraction B [in wt %],
[0201] MFR(A) is the melt flow rate MFR2 (230°C) [g / 10min] of polymer fraction A,
[0202] MFR(CP) is the melt flow rate MFR2 (230°C) [g / 10min] of the C3C4 random copolymer,
[0203] MFR(B) is the calculated melt flow rate of polymer fraction B, MFR2 (230° C.) [g / 10 min].
[0204] Quantitative Study on the Microstructure of Propylene-1-Butene Copolymers by NMR Spectroscopy
[0205] Quantitative nuclear magnetic resonance (NMR) spectroscopy was used to quantify the comonomer content of the polymers.
[0206] Use for 1 H and 13 Quantitative measurements were recorded in the melt on a Bruker Advance III500 NMR spectrometer operating at 500.13 and 125.76 MHz, respectively. 13 C{ 1 H} NMR spectroscopy. Nitrogen was used for all pneumatics, using 13All spectra were recorded at 180 °C using a C-optimized 7 mm magic angle spinning (MAS) probe. Approximately 200 mg of material was loaded into a 7 mm outer diameter zirconium oxide MAS rotor and spun at a frequency of 4 kHz. This setup was chosen primarily because of the high sensitivity required for rapid identification and accurate quantification {klimke06,parkinson07,castignolles09}. Standard single pulse excitation was used with NOE with short recycle delay {pollard04,klimke06} and RS-HEPT decoupling scheme {fillip05,griffin07}. A total of 1024 (1k) transients were acquired for each spectrum using a 3 s recycle delay.
[0207] Quantitative 13 C{ 1 H} NMR spectra were processed, integrated and the relevant quantitative properties determined from the integration. All chemical shifts were internally referenced to the methyl isotactic pentad (mmmm) at 21.85 ppm {randall89}.
[0208] Basic comonomer content method spectral analysis method:
[0209] A characteristic signal corresponding to 1-butene incorporation was observed {randall89} and the comonomer content was quantified in the following manner.
[0210] The amount of 1-butene incorporated in the PPBPP isolated sequence was quantified using the integral at the αB2 site at 43.6 ppm accounting for the number of reported sites per comonomer:
[0211] B=I α / 2
[0212] The amount of 1-butene incorporated into the PPBBPP bicontinuous sequence was quantified using the integration of the ααB2B2 sites at 40.5 ppm accounting for the number of reported sites for each comonomer:
[0213] BB=2*I αα
[0214] When bicontinuous incorporation is observed, the amount of 1-butene incorporated in the PPBPP isolated sequence needs to be compensated due to the overlap of the signals αB2 and αB2B2 at 43.9 ppm:
[0215] B=(I α –2*I αα ) / 2
[0216] The total 1-butene content was calculated based on the sum of isolated and continuously incorporated 1-butene:
[0217] B 总 =B+BB
[0218] The amount of propylene is quantified based on the relative amounts of the primary Sαα methylene site at 46.7 ppm and compensating for the unaccounted αB2 and αB2B2 methylene units of propylene (note the B and BB counts for the butene monomers per sequence are not the number of sequences):
[0219] P 总 =IS αα +B+BB / 2
[0220] The total mole fraction of 1-butene in the polymer was then calculated as:
[0221] f B =B 总 / (B 总 +P 总 )
[0222] The complete integrated equation for the mole fraction of 1-butene in the polymer is:
[0223] f B =(((I α –2*I αα ) / 2)+(2*I αα )) / (IS αα +((Iα–2*I αα ) / 2)+((2*I αα ) / 2))
[0224] +((I α –2*I αα ) / 2)+(2*I αα ))
[0225] This simplifies to:
[0226] f B =(I α / 2+I αα ) / (IS αα +I α +I αα )
[0227] The total incorporation of 1-butene in mole percent is calculated in the usual manner from the mole fractions:
[0228] B [mol%] = 100*f B
[0229] The total incorporation of 1-butene in weight percent is calculated from the mole fraction in the standard manner:
[0230] B [weight %] = 100 * (f B *56.11) / ((f B*56.11)+((1-f B )*42.08))
[0231] Details of these operations can be found in the following literature: Katja Klimke, Matthew Parkinson, Christian Piel, Walter Kaminsky Hans Wolfgang Spiess, Manfred Wilhelm, Macromol. Chem. Phys. 2006, 207, 382; Matthew Parkinson, Katja Klimke, Hans Wolfgang Spiess, Manfred Wilhelm, Macromol. Chem. Phys. 2007, 208, 2128; Patrice Castignolles, Robert Graf, Matthew Parkinson, Manfred Wilhelm, Marianne Gaborieau:, Polymer 2009, 50, 2373; M. Pollard, K. Klimke, R. Graf, HW Spiess, M. Wilhelm, O. Sperber, C. Piel, W. Kaminsky, Macromolecules 2004, 37, 813; Xenia Filip, Carmen Tripon,Claudiu Filip,J.Magn.Reson.2005,176,239;John M.Griffin,CarmenTripon,Ago Samoson,Claudiu Filip,Steven P.Brown,Mag.Res.in Chem.2007,45(S1),S198;J.Randall Rev.Macromol.Chem.Phys.1989,C29,201.
[0232] Mn, Mw, MWD
[0233] The molecular weight averages (Mz, Mw and Mn), the molecular weight distribution (MWD) and its breadth, described by the polydispersity index, PDI = Mw / Mn (where Mn is the number average molecular weight and Mw is the weight average molecular weight) are determined by gel permeation chromatography (GPC) according to ISO 16014-1:2003, ISO 16014-2:2003, ISO 16014-4:2003 and ASTM D 6474-12 using the following formula:
[0234]
[0235]
[0236]
[0237] For a constant elution volume interval ΔVi, where Ai and Mi are the chromatographic peak slice area and polyolefin molecular weight (MW), respectively, associated with the elution volume Vi, and where N equals the number of data points obtained from the chromatogram between the integration limits.
[0238] A high temperature GPC instrument was used, equipped with an infrared (IR) detector (IR4 or IR5 from PolymerChar (Valencia, Spain)) or a differential refractometer (RI) from Agilent Technologies, equipped with 3×Agilent-PLgel Olexis and 1×Agilent-PLgel Olexis Guard columns. As solvent and mobile phase, 1,2,4-trichlorobenzene (TCB) stabilized with 250 mg / L 2,6-di-tert-butyl-4-methyl-phenol was used. The chromatographic system was operated at 160°C and a constant flow rate of 1 mL / min. 200 μL of sample solution was injected for each analysis. Data collection was performed using Agilent Cirrus software version 3.3 or PolymerChar GPC-IR control software.
[0239] The column set was calibrated using a universal calibration (according to ISO 16014-2:2003) with 19 narrow MWD polystyrene (PS) standards ranging from 0.5 kg / mol to 11500 kg / mol. The PS standards were dissolved at room temperature for several hours. The conversion of polystyrene peak molecular weight to polyolefin molecular weight was accomplished by using the Mark Houwink equation and the following Mark Houwink constants:
[0240] K PS =19x10 -3 mL / g,α PS =0.655
[0241] K PE =39x10 -3 mL / g,α PE =0.725
[0242] K PP =19x10 -3 mL / g,α PP =0.725
[0243] A third-order polynomial fit was used to fit the calibration data.
[0244] All samples were prepared in the concentration range of 0.5-1 mg / ml and dissolved at 160°C with constant gentle shaking for 2.5 hours (for PP) or 3 hours (for PE).
[0245] Comonomer content of 1-butene and 1-hexene in linear low density polyethylene (mLLDPE)
[0246] Use for 1 H and 13 Quantitative measurements were recorded in the melt on a Bruker Advance III500 NMR spectrometer operating at 500.13 and 125.76 MHz, respectively. 13 C{ 1 H} NMR spectroscopy. Nitrogen was used for all pneumatics, using 13All spectra were recorded at 150°C using a C optimized 7 mm magic angle spinning (MAS) probe. Approximately 200 mg of material was loaded into a 7 mm outer diameter zirconium oxide MAS rotor and spun at a frequency of 4 kHz. This setup was chosen primarily because of the high sensitivity required for rapid identification and accurate quantification (Klimke, K., Parkinson, M., Piel, C., Kaminsky, W., Spiess, H. W., Wilhelm, M., Macromol. Chem. Phys. 2006; 207: 382., Parkinson, M., Klimke, K., Spiess, H. W., Wilhelm, M., Macromol. Chem. Phys. 2007; 208: 2128., Castignolles, P., Graf, R., Parkinson, M., Wilhelm, M., Gaborieau, M., Polymer 50 (2009) 2373). Transient NOE with a short recycle delay of 3 seconds (Pollard, M., Klimke, K., Graf, R., Spiess, H. W., Wilhelm, M., Sperber, O., Piel, C., Kaminsky, W., Macromolecules 2004; 37: 813., Klimke, K., Parkinson, M., Piel, C., Kaminsky, W., Spiess, H. W., Wilhelm, M., Macromol. Chem. Phys. 2006; 207: 382.) and the RS-HEPT decoupling scheme (Filip, X., Tripon, C., Filip, C., J. Mag. Resn. 2005, 176, 239, Griffin, J. M., Tripon, C., Samoson, A., Filip, C., and Brown, S. P., Mag. Res. in Chem. 2007 45, S1, S198) using standard single pulse excitation. A total of 1024 (1k) transients were acquired for each spectrum. This setting was chosen because of its high sensitivity to low comonomer contents.
[0247] A custom-made automated spectroscopic analysis program was used to quantify 13 C{ 1 H} NMR spectra were processed, integrated and quantitatively characterized. All chemical shifts were internally referenced to the bulk methylene signal (δ+) at 30.00 ppm (J. Randall, Macromol. Sci., Rev. Macromol. Chem. Phys. 1989, C29, 201).
[0248] The amount of ethylene is quantified using the integration of the methylene (δ+) sites at 30.00 ppm accounting for the number of reported sites per monomer:
[0249] E=I δ+ / 2
[0250] Correction for the presence of isolated comonomer units based on the number of isolated comonomer units present:
[0251] E 总 =E+(3*B+2*H) / 2
[0252] wherein B and H are defined with respect to their respective comonomers. Correction for continuous and discontinuous comonomer incorporation (when present) is performed in a similar manner.
[0253] A characteristic signal corresponding to 1-butene incorporation was observed (J. Randall, Macromol. Sci., Rev. Macromol. Chem. Phys. 1989, C29, 201.) and all levels were calculated relative to all other monomers present in the polymer.
[0254] The amount of isolated 1-butene incorporated into the EEBEE sequence was quantified using the integration of the *B2 site at 38.3 ppm accounting for the number of reported sites per monomer:
[0255] B=I *B2
[0256] The amount of 1-butene continuously incorporated in the EEBBEE sequence was quantified using the integration of the ααB2B2 sites at 39.4 ppm, which accounts for the number of reporting sites per monomer:
[0257] BB=2*I ααB2B2
[0258] The amount of non-continuous incorporation of 1-butene in the EEBEBEE sequence was quantified using the integration of the ββB2B2 site at 24.7 ppm accounting for the number of reporting sites per monomer:
[0259] BEB=2*I ββB2B2
[0260] Since the *B2 and *βB2B2 sites of isolated (EEBEE) and discontinuously incorporated (EEBEBEE) 1-butenes respectively overlap, the total amount of isolated 1-butene incorporation was corrected based on the amount of discontinuous 1-butene present:
[0261] B=I *B2 -2*I ββB2B2
[0262] The total 1-butene content was calculated based on the sum of isolated, continuous and discontinuously incorporated 1-butene:
[0263] B 总 =B+BB+BEB
[0264] The total mole fraction of 1-butene in the polymer was then calculated as:
[0265] fB=(B 总 ) / (E 总 +B 总 +H 总 )
[0266] A characteristic signal corresponding to 1-hexene incorporation was observed (J. Randall, Macromol. Sci., Rev. Macromol. Chem. Phys. 1989, C29, 201.) and all levels were calculated relative to all other monomers present in the polymer.
[0267] The amount of isolated 1-hexene incorporated into the EEHEE sequence was quantified using the integration of the *B4 site at 39.9 ppm accounting for the number of reporting sites per monomer:
[0268] H=I *B4
[0269] The amount of 1-hexene incorporated continuously in the EEHHEE sequence was quantified using the integration of the ααB4B4 sites at 40.5 ppm accounting for the number of reporting sites per monomer:
[0270] HH=2*I ααB4B4
[0271] The amount of non-continuous incorporation of 1-hexene in the EEHEHEE sequence was quantified using the integration of the ββB4B4 sites at 24.7 ppm accounting for the number of reporting sites per monomer:
[0272] HEH=2*I ββB4B4
[0273] Since the ββB2B2 sites of the discontinuously incorporated (EEBEBEE) 1-butene and the ββB4B4 sites of the discontinuously incorporated (EEHEHEE) 1-hexene overlap, the total amount of the discontinuously incorporated (EEBEBEE) 1-butene is assumed to be proportional to the amount of isolated 1-butene (B) insertions, and the total amount of the discontinuously incorporated (EEHEHEE) 1-hexene is assumed to be proportional to the amount of isolated 1-hexene (H).
[0274] The total mole fraction of 1-hexene in the polymer was then calculated as:
[0275] f H =(H总 ) / (E 总 +B 总 +H 总 )
[0276] The mole percent comonomer incorporation is calculated from the mole fraction:
[0277] B [mol %] = 100 * fB
[0278] H [mol %] = 100 * fH
[0279] The weight percent comonomer incorporation is calculated from the mole fraction:
[0280] B [weight %] = 100 * (fB * 56.11) / ((fB * 56.11) + (fH * 84.16) + ((1 - (fB + fH)) * 28.05))
[0281] H [weight %] = 100 * (fH * 84.16) / ((fB * 56.11) + (fH * 84.16) + ((1 - (fB + fH)) * 28.05))
[0282] density
[0283] Density was measured according to ISO 1183-187. Sample preparation was done by compression molding according to ISO 1872-2:2007.
[0284] Differential Scanning Calorimetry (DSC)
[0285] Differential scanning calorimetry (DSC) analysis, melting temperature (T m ) and melting enthalpy (H m ), crystallization temperature (T c ) and heat of crystallization (H c The DSC was run according to ISO 11357 / Part 3 / Method C2 in a heating / cooling / heating cycle with a scan rate of 10°C / min in the temperature range of -30 to +225°C. The crystallization temperature (T c ) and heat of crystallization (H c ), while the melting temperature (T m ) and melting enthalpy (H m ).
[0286] Xylene cold soluble matter (XCS) content
[0287] The xylene cold soluble fraction (XCS, wt. %) at room temperature was determined according to ISO 16152; 5th edition; 2005-07-01 at 25°C.
[0288] C6 FDA
[0289] It is measured according to FDA section 177.1520. 1 g of a 100 μm thick polymer film is added to 400 ml of hexane at 50°C for 2 hours while stirring with a reflux cooler. The mixture is immediately filtered on filter paper after 2 hours. The precipitate is collected in an aluminum container and the residual hexane is evaporated on a steam bath under a stream of N2. The amount of hexane solubles is determined by the formula ((sample weight + crucible weight) - (crucible weight)) / (sample weight) × 100%.
[0290] Tensile modulus
[0291] The tensile modulus in the machine direction and in the transverse direction was determined according to ISO 527-3 at 23° C. on the multilayer films produced as shown below. The test was carried out at a crosshead speed of 1 mm / min.
[0292] Dart Drop Intensity (DDI)
[0293] The dart drop was measured using ASTM D1709 Method A (Alternative Testing Technique) from a multilayer film produced as shown below. A dart with a hemispherical head of 38 mm diameter was dropped from a height of 0.66 m onto the multilayer film clamped over a hole. Successive groups of twenty specimens were tested. One weight was used per group, and the weight was increased (or decreased) from group to group in uniform increments. The weight that caused 50% of the specimens to fail was calculated and reported.
[0294] Haze and transparency
[0295] The haze and clarity were measured according to ASTM D 1003-00 on the multilayer films produced as shown below.
[0296] Opto-Mechanical Ability (OMA)
[0297] Optomechanical Ability (OMA) is understood as the ratio of mechanical (especially dart drop intensity (DDI) and tensile (MD)) properties to optical properties (i.e. haze), where the mechanical properties aim to be as high as possible, while the optical properties in terms of haze are desired to be as low as possible.
[0298] The photomechanical ability (OMA) is determined according to the following formula:
[0299]
[0300] Sealing Initiation Temperature (SIT)
[0301] The heat seal initiation temperature (SIT) is the seal temperature at which a seal strength of >5N is achieved.
[0302] The sealing range of the multilayer films produced as shown below was determined on a J&B Universal Sealing Machine Model 3000 using the following parameters:
[0303] Sample width: 25.4mm
[0304] Sealing pressure: 0.1N / mm 2
[0305] Sealing time: 0.1 seconds
[0306] Cooldown: 99 seconds
[0307] Peeling speed: 10mm / sec
[0308] Starting temperature 80℃
[0309] End temperature: 150℃
[0310] Increment: 10℃
[0311] The samples were sealed from A to A at each seal bar temperature and the seal strength (force) was determined at each step.
[0312] Determine the temperature at which the seal strength reaches 5N
[0313] 2. Example
[0314] 2.1. Catalyst system used in the embodiments of the present invention
[0315] Catalysts for mLLDPE in the sealing layer (SL) and outer layer (OL)
[0316] The catalyst used to produce mLLDPE of the sealing layer (SL) and outer layer (OL) of IE2 and IE3 is a metallocene catalyst having a metallocene complex bis(1-methyl-3-n-butylcyclopentadienyl)Zr(IV)Cl2 (CAS No. 151840-68-5) supported on a carrier.
[0317] 130 grams of the metallocene complex bis(1-methyl-3-n-butylcyclopentadienyl)zirconium dichloride (IV) (CAS No. 151840-68-5) and 9.67 kg of a 30% commercial solution of methylaluminoxane (MAO) in toluene were combined and 3.18 kg of dried purified toluene were added. Thus, the obtained composite solution was added to 17 kg of silica support Sylopol 55 SJ (supplied by Grace) by very slow uniform spraying over 2 hours. The temperature was kept below 30° C. After the addition of the complex, the mixture was reacted at 30° C. for 3 hours.
[0318] Catalyst for propylene-1-butene copolymer for core layer (CL)
[0319] The catalyst used in the polymerization process of the C3C4 random copolymer composition for the core layer (CL) of IE1 to IE3 was prepared as follows:
[0320] Metallocene (MC1) (rac-trans-dimethylsilanediyl(2-methyl-4-phenyl-5-methoxy-6-tert-butyl-indenyl)(2-methyl-4-(4-tert-butylphenyl)indenyl)zirconium dichloride) was synthesized as described in WO 2013 / 007650.
[0321] The catalyst was prepared according to Catalyst 3 of WO 2015 / 11135 using a catalyst system of metallocene MC1, MAO and trityltetrakis(pentafluorophenyl)borate, provided that the surfactant was 2,3,3,3-tetrafluoro-2-(1,1,2,2,3,3,3-heptafluoropropoxy)-1-propanol.
[0322] 2.2.a) Preparation of propylene-1-butene copolymer for core layer (CL)
[0323] The copolymers used in the core layer (CL) of the inventive examples (IE1 to IE3) were prepared in a two-stage polymerization process using the catalyst defined above under the conditions listed in Table 1. The properties of the various fractions and the final multimodal copolymers are also listed in Table 1.
[0324] Table 1: Production data of bimodal propylene-1-butene random copolymers from IE1 to IE3 (CL)
[0325]
[0326]
[0327] The pelletization of the copolymer was carried out on a ZSK 32 twin-screw extruder. The required amount of copolymer powder, additives (1000 ppm of Irganox B215 supplied by BASF, a 1:2 mixture of pentaerythritol tetrakis(3-(3',5'-di-tert-butyl-4-hydroxyphenyl)propionate (CAS No. 6683-19-8) and tris(2,4-di-tert-butylphenyl)phosphite (CAS No. 31570-04-4), and 500 ppm of calcium stearate from Baerlocher) were mixed and extruded at 220° C. with a throughput of 100 kg / h.
[0328] 2.2.b) Preparation of metallocene-catalyzed linear low-density polyethylene (mLLDPE) for sealing and outer layers (SL, OL)
[0329] In a process comprising a prepolymerization loop reactor, two loop reactors and a gas phase reactor The polymerization was carried out in a PE3G unit, wherein the slurry from the prepolymerization reactor was intermittently withdrawn and introduced into the first loop reactor, and then the slurry was intermittently withdrawn from the second loop reactor by using settling legs and introduced into a flash vessel operated at a temperature of 50°C and a pressure of 3 bar, and the polymer was then directed from there to a gas phase reactor (GPR)
[0330] The polymerization conditions can be seen in Table 2:
[0331] Table 2: mLLDPE production data for IE2 (mLLDPE2) and IE3 (mLLDPE3)
[0332]
[0333]
[0334]
[0335] The polymer was mixed with 0.2 wt% Irganox B561. They were then kneaded and extruded into pellets using a CIMP90 extruder under a nitrogen atmosphere to achieve an SEI of 230 kWh / kg and a melt temperature of 250°C.
[0336] 2.3. Film compositions IE1 to IE3, CE1
[0337] All films are 3-layer blown films with a seal layer (SL), a core layer (CL) and an outer layer (OL)
[0338] Inventive embodiment 1 (IE1):
[0339] The sealing layer (SL) and the outer layer (OL) are made of 90.0 wt% mLLDPE1 and 10.0 wt% LDPE, wherein
[0340] mLLDPE1 is Example IE1 of EP 3 257 895 A1, with a 1-butene content of 0.3 mol%, a 1-hexene content of 2.6 mol%, and a density of 0.918 g / cm 3 , melt flow rate MFR2 (190℃, 2.16kg) is 1.5g / 10min;
[0341] as well as
[0342] LDPE is Borealis' low-density polyethylene "FT5230", with a density of 923g / cm 3 , melt flow rate MFR2 (190°C, 2.16kg) is 0.75g / 10min;
[0343] The core layer (CL) is made of the propylene-1-butene copolymer (PBC) prepared as described above.
[0344] Inventive embodiment 2 (IE2):
[0345] The sealing layer (SL) and the outer layer (OL) are made of 90.0 wt% mLLDPE2 and 10.0 wt% LDPE, wherein
[0346] mLLDPE2 was prepared as described above. LDPE was low-density polyethylene "FT5230" from Borealis AG with a density of 923 g / cm 3 , melt flow rate MFR2 (190℃, 2.16kg) is 0.75g / 10min
[0347] The core layer (CL) is made of the propylene-1-butene copolymer (PBC) prepared as described above.
[0348] Inventive embodiment 3 (IE3):
[0349] The sealing layer (SL) and the outer layer (OL) are made of 90.0 wt% mLLDPE3 and 10.0 wt% LDPE, wherein
[0350] mLLDPE3 was prepared as described above. LDPE was low-density polyethylene "FT5230" from Borealis AG with a density of 923 g / cm 3 , melt flow rate MFR2 (190℃, 2.16kg) is 0.75g / 10min
[0351] The core layer (CL) is made of the propylene-1-butene copolymer (PBC) prepared as described above.
[0352] Comparative Example 1 (CE1):
[0353] The sealing layer (SL) and the outer layer (OL) are made of 90.0 wt% mLLDPE1 and 10.0 wt% LDPE, wherein
[0354] mLLDPE1 is Example IE1 of EP 3 257 895 A1, with a 1-butene content of 0.3 mol%, a 1-hexene content of 2.6 mol%, and a density of 0.918 g / cm 3 , melt flow rate MFR2 (190℃, 2.16kg) is 1.5g / 10min;
[0355] LDPE is Borealis' low-density polyethylene "FT5230", with a density of 923g / cm 3 , melt flow rate MFR2 (190°C, 2.16kg) is 0.75g / 10min;
[0356] The core layer (CL) is made of commercially available polypropylene ethylene random copolymer RB707CF from Borealis Chemicals AG, with a melt flow rate MFR2 (230°C) of 1.5 g / 10 min and a melting temperature T m It is 145℃.
[0357] Mixing of sealing layer (SL) and outer layer (OL) materials (M)
[0358] Melt mixing was performed in a Thermo Fisher (PRISM) TSE 24 twin-screw extruder at 220°C, and the resulting melt strands were solidified in a water bath and pelletized.
[0359] Membrane production
[0360] Three-layer blown polymer films were produced on a three-layer Collin laboratory-scale blown film line. The melting temperatures of the sealing layer (SL) and the outer layer (OL) were 185°C to 195°C. The melting temperature of the core layer (CL) was in the range of 205°C to 215°C. The production capacity of the extruder amounted to 80 kg / h. The film structure was SL-CL-OL, the core layer was 25 μm (CL), and the sealing layer (SL) and the outer layer (OL) were 12.5 μm. The layer thicknesses were determined by scanning electron microscopy. The materials used for the layers of the multilayer film are listed in Table 3. The properties of the multilayer film are listed in Table 4.
[0361] Table 3: Layer structure of multilayer films
[0362]
[0363] Table 4: Multilayer film properties
[0364]
[0365]
[0366] It can be clearly seen from the above table that the multilayer blown films of the present invention based on a specific core layer (CL) show much higher DDI and improved overall properties, ie high OMA, compared to the comparative examples with similar stiffness.
[0367] Furthermore, using a combination of a specific core layer (CL) and sealing and outer layers (SL, OL) based on trimodal mLLDPE2 and mLLDPE3, improved sealing properties, ie very low SIT, can be obtained.
Claims
1. A multilayer blown film comprising at least two layers, a sealing layer (SL) and a base layer (BL), wherein a) The sealing layer (SL) comprises (i) at least 90.0 wt.-% up to 100.0 wt.-% of a first polymer composition (PC1), based on the total weight of the sealing layer (SL), the first polymer composition comprising at least 70.0 wt.-% up to 100.0 wt.-% of a metallocene-catalyzed linear low density polyethylene (mLLDPE), based on the total weight of the first polymer composition (PC1), and 0.0 up to 30.0 wt.-% of a further polyethylene polymer being a low density polyethylene (LDPE) having a long chain branching (LCB) structure, based on the total weight of the first polymer composition (PC1), the metallocene-catalyzed linear low density polyethylene (mLLDPE) having a density measured according to ISO 1183-187 in the range of 0.890 to 0.930 g / cm 3 within the range, and (ii) 0.0 to up to 10.0 wt. % of an additive (AD) selected from antioxidants, light stabilizers, acid scavengers, processing aids, antiblocking aids, nucleating agents, slip agents and mixtures thereof, based on the total weight of the sealing layer (SL), and b) The base layer (BL) comprises (iii) at least 90.0 wt% up to 100.0 wt% of a metallocene-catalyzed bimodal propylene-1-butene random copolymer, based on the total weight of the base layer (BL), and (iv) 0.0 to up to 10.0 wt. % of an additive (AD) selected from antioxidants, light stabilizers, acid scavengers, processing aids, anti-blocking aids, nucleating agents, slip agents and mixtures thereof, based on the total weight of the base layer (BL).
2. The multilayer blown film according to claim 1, wherein the multilayer blown film comprises at least one further layer in addition to the one sealing layer (SL) and the one base layer (BL), the one further layer being an outer layer (OL), the stacking sequence being sealing layer / base layer / outer layer, (SL) / (BL) / (OL), whereby c) The outer layer (OL) comprises (v) at least 90.0 wt.-%, based on the total weight of the outer layer (OL), of a second polymer composition (PC2), said second polymer composition (PC2) comprising at least 90.0 wt.-%, based on the total weight of the second polymer composition (PC2), of polyethylene or polypropylene, and (vi) 0.0 to up to 10 wt. % of additives (AD) selected from antioxidants, light stabilizers, acid scavengers, processing aids, antiblocking aids, nucleating agents, slip agents and mixtures thereof, based on the total weight of the outer layer (OL).
3. The multilayer blown film according to claim 1 or 2, wherein the propylene-1-butene copolymer a. comprising, based on the total weight of the propylene-1-butene copolymer, 85.0 to 98.0 wt% of propylene and 2.0 to 15.0 wt% of 1-butene, and b. having an MFR2 in the range of 0.5 g / 10 min to less than 4.0 g / 10 min, measured according to ISO 1133 at 230° C. and 2.16 kg load.
4. The multilayer blown film of claim 3, wherein the propylene-1-butene copolymer comprises: 30.0 to 70.0 wt% of a propylene-1-butene copolymer (A) having an MFR2 of 0.5 to 20.0 g / 10 min and a 1-butene content of 2.0 to 10.0 wt%; and 70.0 to 30.0 wt% of a propylene-1-butene copolymer (B) having an MFR2 of 0.5 to 20.0 g / 10 min and a 1-butene content of 3.5 to 20.0 wt%; The copolymers (A) and (B) are different and the amounts of (A) and (B) add up to 100.0% by weight.
5. The multilayer blown film according to claim 1 or 2, wherein the metallocene-catalyzed linear low density polyethylene (mLLDPE) is a bimodal polyethylene terpolymer comprising at least (i) an ethylene polymer component (A) as a lower molecular weight (LMW) component having an MFR2 of 1.0 to 10.0 g / 10 min, measured at 190°C and 2.16 kg load according to ISO 1133, and (ii) as the higher molecular weight (HMW) component an ethylene polymer component (B) having an MFR2 of from 0.2 to 0.9 g / 10 min, measured at 190° C. and 2.16 kg load according to ISO 1133, The density of the ethylene polymer component (A) is higher than that of the ethylene polymer component (B); the density of the ethylene polymer component (A) is between 0.930 and 0.950 g / cm 3 within the range.
6. The multilayer blown film according to claim 1 or 2, wherein the metallocene-catalyzed linear low density polyethylene (mLLDPE) is a trimodal polyethylene terpolymer comprising at least (i) between 10 and <25 wt% of an ethylene polymer component (A) having an MFR2 of 0.1 to 10.0 g / 10 min, measured at 190°C and 2.16 kg load according to ISO 1133, and (ii) between 10 and <25 wt% of an ethylene polymer component (B) having an MFR2 of 2.0 to 150.0 g / 10 min, measured at 190°C and 2.16 kg load according to ISO 1133, and (iii) between >50 and 80 wt% of an ethylene polymer component (C) having an MFR2 of 0.1 to 5.0 g / 10 min, measured at 190°C and 2.16 kg load according to ISO 1133, and The density of the ethylene polymer components (A) and (B) is respectively in the range of 0.925-0.970 g / cm 3 and the density of the ethylene polymer component (C) is between 0.880 and 0.920 g / cm 3 between.
7. The multilayer blown film according to claim 1 or 2, wherein the low density polyethylene (LDPE) is derived from a high pressure polymerization process, wherein the low density polyethylene (LDPE) has a molecular weight of 0.910 to 0.940 g / cm 3 The present invention has a density in the range of 0.05 to 2.0 g / 10 min, and a melt flow rate MFR2 measured according to ISO 1133 at 190° C. and 2.16 kg load.
8. The multilayer blown film according to claim 2, wherein the second polymer composition (PC2) is the same as the first polymer composition (PC1).
9. The multilayer blown film according to claim 1 or 2, wherein the thickness of the base layer (BL) is in the range of 10 to 250 μm, and the thickness of the sealing layer (SL) and the optional outer layer (OL) is in the range of 0.5 to 50 μm, whereby the thickness of each of the sealing layer (SL) and the optional outer layer (OL) is less than the thickness of the base layer (BL).
10. The multilayer blown film according to claim 1 or 2, wherein the tensile modulus of the film is in the range of 400-1200 MPa, measured according to ISO 527 at 23°C on a multilayer blown film having a thickness of 50 μm in the machine direction and in the transverse direction.
11. The multilayer blown film according to claim 1 or 2, wherein the film has a seal initiation temperature (SIT) in the range of 55°C and 100°C, measured on a 50 μm multilayer blown film.
12. The multilayer blown film according to claim 1 or 2, wherein the film has a haze ranging from 0.5% to less than 10.0%, measured according to ASTM D 1003-00 on a 50 μm multilayer blown film.
13. The multilayer blown film according to claim 1 or 2, wherein the film has a transparency of at least 95.0% and up to 100.0%, measured according to ASTM D1003-00 on a blown film having a thickness of 50 μm.
14. The multilayer blown film of claim 1 or 2, wherein the film has a dart drop impact strength (DDI) of at least 150 g up to 550 g as measured according to ASTM D1709 Method A on a 50 μm multilayer blown film.
15. The multilayer blown film according to claim 1 or 2, wherein the film has a photomechanical ability (OMA) of at least 30000 [MPa*g / %] to at most 90000 [MPa*g / %] determined according to the following formula: It was determined on 50 μm multilayer blown films.
Citation Information
Patent Citations
Multi-layered polymer film
EP2994309A1
Bi- or multimodal polyethylene terpolymer with enhanced rheological properties
EP3257895A1
Transparent, stiff and printable polypropylene blown films
WO2007085283A1
catalysts
WO2013007650A1
process
WO2015011135A1